2020
DOI: 10.1016/j.molcel.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

HORMA Domain Proteins and a Trip13-like ATPase Regulate Bacterial cGAS-like Enzymes to Mediate Bacteriophage Immunity

Abstract: Bacteria are continually challenged by foreign invaders, including bacteriophages, and have evolved a variety of defenses against these invaders. Here, we describe the structural and biochemical mechanisms of a bacteriophage immunity pathway found in a broad array of bacteria, including E. coli and Pseudomonas aeruginosa. This pathway uses eukaryoticlike HORMA domain proteins that recognize specific peptides, then bind and activate a cGAS/DncV-like nucleotidyltransferase (CD-NTase) to generate a cyclic triaden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 55 publications
(85 reference statements)
3
168
0
Order By: Relevance
“…Revealing the biochemical basis of Pch2-recruitment to chromosomes, and understanding whether additional regulation drives the switch of Pch2 from ‘monomeric’ C-Hop1 to chromosome-associated C-Hop1 are questions that warrant investigation. Finally, the fact that two checkpoint cascades that respond to distinct chromosomal defects show analogous biochemical signaling logic raises fascinating questions regarding the evolutionary history and origin of these essential signaling pathways [71].…”
Section: Resultsmentioning
confidence: 99%
“…Revealing the biochemical basis of Pch2-recruitment to chromosomes, and understanding whether additional regulation drives the switch of Pch2 from ‘monomeric’ C-Hop1 to chromosome-associated C-Hop1 are questions that warrant investigation. Finally, the fact that two checkpoint cascades that respond to distinct chromosomal defects show analogous biochemical signaling logic raises fascinating questions regarding the evolutionary history and origin of these essential signaling pathways [71].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a cGAS (cyclic GMP-AMP synthase)-like enzyme in a bacterial defense module synthesizes a cyclic GMP-AMP in response to phage infection, which leads to membrane degradation by a phospholipase and cell death (122). A recent study also reported that a cGAS/DncV-like nucleotidyltransferase (CD-NTase) could synthesize cOA3 , which in turn could bind and activate NucC, a DNA nuclease (123). Thus, insights into the cOA signaling pathway in Type III CRISPR-Cas systems may reveal concepts that are broadly applicable to other cyclic nucleotide-based antiphage signaling systems in prokaryotes.…”
Section: Comparison Of Type III Crispr-cas Systems With Other Nucleotmentioning
confidence: 99%
“…The importance of cyclic nucleotide signalling in prokaryote anti-viral defence systems is an emerging paradigm. Examples include cA4 and cA6 for type III CRISPR (5,6), cA3 for the HORMA-DncV-NucC system (24,25) and a variety of cyclic dinucleotides synthesised by diverse CBASS enzymes (26,27). Viruses have a clear imperative to degrade these molecules and circumvent immunity, but it is increasing apparent that cellular immune systems also need a mechanism to turnover these second messengers if they are to prevent runaway toxicity and cell death (13).…”
Section: Discussionmentioning
confidence: 99%